Electrode modifications to lower electrode impedance and improve neural signal recording sensitivity. (23rd September 2015) - Chung, T; Wang, J Q; Wang, J; Cao, B; Li, Y; Pang, S W
Abstract: Objective. Although electrode size should be miniaturized to provide higher selectivity for neural signal recording and to avoid tissue damage, small sized electrodes induce high impedance, which decreases recording quality. In this work, the electrode surface was modified to increase the effective surface area to lower the electrode impedance and to improve the neural signal detection quality by optimizing plasma conditions. Approach. A tetrafluoromethane (CF4 ) plasma was used to increase the effective surface area of gold electrode sites of polyimide-based neural probes. In vitro electrode impedance and in vivo neural signal recording and stimulation were characterized. Main results. For 15 μ m diameter (dia.) electrode size, the average surface roughness could be increased from 1.7 to 22 nm after plasma treatment, and the electrode impedance was decreased by 98%. Averaged background noise power in the range of 1 to 1000 Hz was decreased to −106 dB after the 30 μ m dia. electrodes were plasma modified—lower than the noise level of −86 dB without plasma treatment. Neural probes with plasma-modified electrode sites of 15 and 30 μ m dia. were implanted to the anterior cingulate cortex (ACC) region for acute recording of spontaneous and electrical evoked local field potential (LFP) of neural signals. Spontaneous LFP recorded in vivo by the plasma-modified electrodes of 30 μ m dia. was two times higher compared to electrodes without treatment. For a stimulation current of 400 μ A, electrically evoked LFP recorded by the plasma-modified electrodes was seven times higher than those without plasma exposure. Significance. A controllable technology was developed to increase the effective surface area of electrodes using a CF4 plasma. Plasma-modified electrodes improved the quality of the neural probe recording and more sensitive to record spontaneous and evoked LFP in the ACC region.